Microvesicles from platelets: novel drivers of vascular inflammation - Vajen, Tanja; Mause, Sebastian F.; Koenen, Rory R. (Thrombosis and Haemostasis, 2015)
Microvesicles are receiving increased attention not only as biomarkers but also as mediators of cell communication and as integral effectors of disease. Platelets present a major source of microvesicles and release these microvesicles either spontaneously or upon activation. Platelet-derived microvesicles retain many features of their parent cells and have been shown to exert modulatory effects on vascular and immune cells. Accordingly, microvesicles from platelets can be measured at increased levels in patients with cardiovascular disease or individuals at risk. In addition, isolated microvesicles from platelets were shown to exert immunomodulatory actions on various cell types. In this review the various aspects of platelet-derived microvesicles including release, clearance, measurement, occurrence during disease and relevance for the pathophysiology of vascular inflammation will be discussed.
Keywords: Platelet; microvesicle; microparticle; vascular inflammation; atherosclerosis